2023
DOI: 10.21037/atm-22-6437
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of differentially expressed genes in diabetic foot ulcer and preliminary experimental verification

Abstract: Background Molecular changes are closely related to the pathogenesis and healing process of diabetic foot ulcers (DFUs), and are crucial for the early prediction and intervention of DFU. Methods Bioinformatics analysis was performed in this study to identify the key differentially expressed genes (DEGs) in DFU, analyze their functions and function modes, and conduct preliminary experimental verification to determine the potential pivotal genes in the pathogenesis of DFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The lncRNA taurine upregulated gene 1 (TUG1) restores EPC function in response to high glucose treatment by regulating miR‐29c‐3p/PDGF‐BB/Wnt signalling, the overexpression of TUG1 significantly increases the expression of the autophagy‐related protein LC3, the autophagy inhibitor CQ attenuates this effect, and the effect of TUG1 on EPCs is at least partially mediated by the autophagy pathway 71 . Bioinformatics analysis identified BNIP3 as a differentially expressed gene in DFU based on the GEO microarray public database, and showed that the BNIP3 gene was highly expressed in DFU and that its expression in HG‐induced HUVECs was significantly upregulated, which indicated that the BNIP3 gene may be a target for the treatment of diabetic foot ulcers 72 . Autophagy as a widely studied programmed cell death, its role in DFUs still needs further study.…”
Section: Autophagy In Dfusmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA taurine upregulated gene 1 (TUG1) restores EPC function in response to high glucose treatment by regulating miR‐29c‐3p/PDGF‐BB/Wnt signalling, the overexpression of TUG1 significantly increases the expression of the autophagy‐related protein LC3, the autophagy inhibitor CQ attenuates this effect, and the effect of TUG1 on EPCs is at least partially mediated by the autophagy pathway 71 . Bioinformatics analysis identified BNIP3 as a differentially expressed gene in DFU based on the GEO microarray public database, and showed that the BNIP3 gene was highly expressed in DFU and that its expression in HG‐induced HUVECs was significantly upregulated, which indicated that the BNIP3 gene may be a target for the treatment of diabetic foot ulcers 72 . Autophagy as a widely studied programmed cell death, its role in DFUs still needs further study.…”
Section: Autophagy In Dfusmentioning
confidence: 99%
“… 71 Bioinformatics analysis identified BNIP3 as a differentially expressed gene in DFU based on the GEO microarray public database, and showed that the BNIP3 gene was highly expressed in DFU and that its expression in HG‐induced HUVECs was significantly upregulated, which indicated that the BNIP3 gene may be a target for the treatment of diabetic foot ulcers. 72 Autophagy as a widely studied programmed cell death, its role in DFUs still needs further study.…”
Section: Autophagy In Dfusmentioning
confidence: 99%
“…Wound healing is frequently mediated by growth factors and cytokines generated by cells stimulated through immune response (9). Long-term high glucose levels cause aberrant expression of several molecules, including vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1 (HIF1), and anti-inflammatory factors (10).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term high glucose levels cause aberrant expression of several molecules, including vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1 (HIF1), and anti-inflammatory factors (10). This leads to bad angiogenesis and prolonged inflammation (9). Although there are numerous diabetic wound therapies available, only a few can improve oxygen delivery at the microvascular level (8).…”
Section: Introductionmentioning
confidence: 99%
“…This process is typically facilitated by growth factors and cytokines released by specialized cells that become activated as part of the immune response. 9 Sawaya et al observed that in cases of DFU, the transcription factors FOMI1 and STAT3, which support the survival of immune cells, are suppressed. This ultimately hinders the process of wound healing in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%